VATIS update : ozone layer protection. Vol. 4, No. 133, Nov-Dec 2015 - UN.ESCAP; Asian and Pacific Centre for Transfer of Technology (APCTT) (UN.ESCAP. Asian and Pacific Centre for Transfer of Technology, 2015)
VATIS Update Ozone Layer Protection is published 6 times a year to keep the readers up to date of most of the relevant and latest technological developments and events in the field of Ozone Layer Protection. The Update is tailored to policy-makers, industries and technology transfer intermediaries. Highlights : Eco-friendly adsorption chiller -- A study on the benefits of R290 over HFCs -- Clean and green vapour degreasing process -- Clean agent fire extinguishing system -- Foam blow molding process -- Researchers study destruction of methyl bromide THE SCIENCE OF OZONE LAYER . 4 -- Scientists study effects of organic compounds-- Some ozone safe chemicals can harm environment-- Impact of climate change on ozone -- Ozone hole over Antarctica -- Restoring depleted stratospheric ozone ODS PHASE-OUT IN INDIA . 6 -- Synthesis Report findings presented at 27th Meeting of the Parties -- TEAP presents report on the full range of alternatives to ODSs -- Eco-friendly adsorption chiller -- HPMP Stage-II IN THE NEWS . 8 -- Pakistan to reduce ozone depleting gases -- Ozone-harming substance imports to drop in Myanmar -- Viet Nam reduces ODS consumption -- 1358 industrial units get rid of ODS in Iran -- Malaysia to phase-out HCFC by 2030 -- EU reports progress on phase-out of ODS -- Maldives limits anti-ozone substances -- Skills competition in refrigeration servicing sector REFRIGERATION/AIR-CONDITIONING . 10 -- Patent for CO2/hydrocarbon refrigerant blend -- A study on the benefits of R290 over HFCs -- Scientist studies benefits of new metal alloy -- Energy efficient multi-blend refrigerant -- Mercedes-Benz develops R1234yf alternative -- HFO/HFC/CO2 hybrid on its way SOLVENTS . 12 -- Clean and green vapour degreasing process -- Environmentally friendly vapour degreasing solvent -- Zero ODP specialty solvent -- Water based cleaner for flux removal -- Environmentally friendly solvent -- CO2 based cleaning solutions HALONS . 14 -- Clean agent fire extinguishing system -- Inert gases fire suppression system -- Process ...